The Atypical Cannabinoid Abn-CBD Reduces Inflammation and Protects Liver, Pancreas, and Adipose Tissue in a Mouse Model of Prediabetes and Non-alcoholic Fatty Liver Disease - Romero-Zerbo, Silvana Y.; García-Fernández, María; Espinosa-Jiménez, Vanesa; Pozo-Morales, Macarena; Escamilla-Sánchez, Alejandro; Sánchez-Salido, Lourdes; Lara, Estrella; Cobo-Vuilleumier, Nadia; Rafacho, Alex; Olveira, Gabriel; Rojo-Martínez, Gemma; Gauthier, Benoit R.; et al. (Frontiers in Endocrinology, 2020)
Background and aims: The synthetic atypical cannabinoid Abn-CBD, a cannabidiol (CBD) derivative, has been recently shown to modulate the immune system in different organs, but its impact in obesity-related meta-inflammation remains unstudied. We investigated the effects of Abn-CBD on metabolic and inflammatory parameters utilizing a diet-induced obese (DIO) mouse model of prediabetes and non-alcoholic fatty liver disease (NAFLD). Materials and Methods: 10-week-old C57Bl/6J mice were fed a high-fat diet for 15 weeks, following a 2-week treatment of daily intraperitoneal injections with Abn-CBD or vehicle. At week 15 mice were obese, prediabetic and developed NAFLD. Body weight and glucose homeostasis were monitored. Mice were euthanized and blood, liver, adipose tissue and pancreas were collected and processed for metabolic and inflammatory analysis. Results: Body weight and triglycerides profiles in blood and liver were comparable between vehicle- and Abn-CBD-treated DIO mice. However, treatment with Abn-CBD reduced hyperinsulinemia and markers of systemic low-grade inflammation in plasma and fat, also promoting white adipose tissue browning. Pancreatic islets from Abn-CBD-treated mice showed lower apoptosis, inflammation and oxidative stress than vehicle-treated DIO mice, and beta cell proliferation was induced. Furthermore, Abn-CBD lowered hepatic fibrosis, inflammation and macrophage infiltration in the liver when compared to vehicle-treated DIO mice. Importantly, the balance between hepatocyte proliferation and apoptosis was improved in Abn-CBD-treated compared to vehicle-treated DIO mice. Conclusions: These results suggest that Abn-CBD exerts beneficial immunomodulatory actions in the liver, pancreas and adipose tissue of DIO prediabetic mice with NAFLD, thus protecting tissues. Therefore, Abn-CBD and related compounds could represent novel pharmacological strategies for managing obesity-related metabolic disorders.